Challenges and Strategies for the Internationalization of Indonesian SMEs in the Global Value Chain in the Digital Age - Agus Fitriadi; Sudarmiatin Sudarmiatin; Heri Pratikto (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
The internationalization of micro, small, and medium-sized enterprises (MSMEs) has become a strategic issue in addressing global economic dynamics, particularly within the framework of the Global Value Chain (GVC) in the digital age. Although Indonesian MSMEs have great potential to support the national economy, their level of involvement in the global value chain remains relatively limited. This study aims to analyze the challenges and strategies for the internationalization of Indonesian MSMEs within the GVC in the digital age. The study employs a qualitative approach using a case study design, along with thematic analysis and value chain analysis techniques. The findings indicate that MSMEs are already involved in the GVC across various stages of the value chain—from raw material processing to global distribution—yet they continue to face numerous challenges, such as technological limitations, human resource competencies, production capacity, and international distribution networks. On the other hand, digitalization has proven to be a key factor in expanding access to global markets through the use of digital platforms. An effective internationalization strategy requires the integration of product innovation based on local resources, the utilization of digital technology, and the strengthening of global business networks. This study contributes to integrating the perspectives of GVCs, digitalization, and SME internationalization strategies into a comprehensive analytical framework, and provides practical implications for SME actors and policymakers in enhancing competitiveness in the global market